Determination of Inactive Powers in a Single-Phase AC Network; Energies; Vol. 14, iss. 16 - Shchurov N. I. Nikolay Ivanovich; Myatezh S. V. Sergey Vladimirovich; Malozemov B. V. Boris Vitaljevich; Shtang A. A. Aleksandr Aleksandrovich; Martyushev N. V. Nikita Vladimirovich; Klyuev R. V. Roman Vladimirovich; Dedov S. I. Sergey Igorevich (2021, 2021)
Title screen